Salt-Dependent Phase Transition Behavior of Doubly Thermoresponsive Poly(sulfobetaine)-Based Diblock Copolymer Thin Films - Kreuzer, Lucas P (Langmuir : the ACS journal of surfaces and colloids, 2021)
The water vapor-induced swelling, as well as subsequent phase-transition kinetics, of thin films of a diblock copolymer (DBC) loaded with different amounts of the salt NaBr, is investigated in situ. In dilute aqueous solution, the DBC features an orthogonally thermoresponsive behavior. It consists of a zwitterionic poly(sulfobetaine) block, namely, poly(4-(N-(3'-methacrylamidopropyl)-N,N-dimethylammonio) butane-1-sulfonate) (PSBP), showing an upper critical solution temperature, and a nonionic block, namely, poly(N-isopropylmethacrylamide) (PNIPMAM), exhibiting a lower critical solution temperature. The swelling kinetics in D2O vapor at 15 °C and the phase transition kinetics upon heating the swollen film to 60 °C and cooling back to 15 °C are followed with simultaneous time-of-flight neutron reflectometry and spectral reflectance measurements. These are complemented by Fourier transform infrared spectroscopy. The collapse temperature of PNIPMAM and the swelling temperature of PSBP are found at lower temperatures than in aqueous solution, which is attributed to the high polymer concentration in the thin-film geometry. Upon inclusion of sub-stoichiometric amounts (relative to the monomer units) of NaBr in the films, the water incorporation is significantly increased. This increase is mainly attributed to a salting-in effect on the zwitterionic PSBP block. Whereas the addition of NaBr notably shifts the swelling temperature of PSBP to lower temperatures, the collapse temperature of PNIPMAM remains unaffected by the presence of salt in the films